Math and science outcomes for students of teachers from standard and alternative pathways in Texas - Michael Marder; Bernard David; Caitlin Hamrock (Arizona State University, 2020)
Texas provides a unique opportunity to examine teachers without standard university preparation, for it prepares more teachers through alternative pathways than any other state. We find two advantages for mathematics and science teachers prepared in the standard way. First, since 2008 they have been staying in the classroom longer than those who pursued alternative routes. Second, we analyze student performance on Algebra 1 and Biology exams over the period 2012-2018. Algebra I students with experienced teachers from standard programs gain .03 to .05 in standard deviation units compared to students whose teachers were alternatively prepared. For Biology students there are fewer statistically significant differences, although when differences exist they almost all favor standard programs. These effects are difficult to measure in part because teachers are not assigned to teach courses with high-stakes exams at random. Nevertheless, we find strong evidence in Algebra I that students learn more when their teachers have standard preparation. In Biology there is also evidence but less compelling. Thus, we recommend that all states bolster traditional university-based teacher certification, that Texas not take drastic action to curtail alternative certification, and that other states not allow it to grow too quickly.